DETERMINATION OF POSSIBLE REASONS OF DEFECT FORMATION «MICROPITTING» IN HARD-ALLOY WIRE DRAWING INSTRUMENT IN WIRE DRAWING PROCESS - T. P. Kurenkova; I. P. Lazebnikova; T. N. Lipatkina (Литьë и металлургия)
It is determined that during operation a hard wear along with uniform attrition occurs in working canal of die because of welding of metal particles to the material of die, what results in formation of separate microholes, their enlargement and further defect creation of type “micropitting of hard alloy”.